THE CONTRIBUTION OF READING COMPREHENSION SKILL TO MATHEMATICS PROBLEM SOLVING STUDENTS OF 11th GRADE HIGH SCHOOLMTA SURAKARTA IN LINEAR PROGRAM MATERIAL - Kusnul Chotimah Dwi Sanhadi; Mardiyana Mardiyana; Ikrar Pramudya (Proceedings Education and Language International Conference, 2017)
This study aims to determine the contribution of reading comprehension skill of students to their mathematics learning outcomes in problem solving linear program material for XI SMA MTA Surakarta academic year 2016/2017. In this study, the ability to understand the reading () serves as the independent variable and the results of students' mathematics learning () as the dependent variable. The population in this study were all students of class XI SMA MTA Surakarta academic year 2016/2017 and the obtained sample were 200 students. Based on descriptive analysis, it is obtained an average score of reading comprehension skill is 62.5142, and for mathematics learning outcomes is 46.5075. Based on the results obtained by analysis of linear regression, it is obtained the alleged regression model obtained means or can be used to predict the results of students’ mathematics learning. From the regression equation estimators obtained, a regression coefficient of 0.706 states that any change in the reading comprehension skill by 1 unit will improve mathematics achievement of 0.706 units. Therefore, it can be concluded that there are significant ability to understand the reading of the results of learning mathematics in solving linear program material positively. Keywords: Mathematics Problem Solving, Reading Comprehension Skill